EFEK PIJAT PUNGGUNG TERHADAP PRODUKSI ASI PADA IBU PASCA BEDAH SESAR - Dewi, Adinda Putri Sari; Dasuki, Djaswadi; Kartini, Farida (Kesmas Indonesia, 2017)
The purpose of this research To find out the effect of back massage  as one of the ways in improving the breast milk production of the post secarean section mothers. The study used Randomized Controlled Trial design. The samples were taken using simple random sampling with a total of  27samples for each group (intervention and control). Bivariat analysis used chi square with a significance level of p <0.05. Multivariate analysis used logistic regression to identify confounding variables to milk production after cesarean section. The results indicate that there is a difference in milk production between the intervention and the control groups with an RR of 1.9 (95% CI: 1.097 to 3.291). Parity and frequency of breastfeeding have significant correlation with breast milk production. Motherâs age, obesity, and in patient have no significant correlation with breast milk production.